The Impact of Union Amalgamation on Membership: An Australian Case Study - Oliver, Bobbie (Sage Publications, 2016)
In 1980s and 1990s, Australian trade unions tried to combat declining influence and membership numbers by amalgamating with other unions in the same or related industries. Much has been written on union mergers, but little on how these affect the membership. This article aims to contribute to the literature of the impact of mergers and amalgamations on members but studying just one union, The West Australian Locomotive Engine Drivers, Firemen’s and Cleaners Union (LEDU; 1898-1999). In 1993, the three federal railway unions—the Australian Railways Union (ARU), the Australian Federated Union of Locomotive Employees (AFULE), and the National Union of Railworkers (NUR), and one bus and tram union, the Australian Tramway & Motor Omnibus Employees Association (ATM)—amalgamated to become the Australian Rail Tram and Bus Industry Union (RTBU). The LEDU reluctantly joined the RTBU in 1999. This article examines rank and file reaction to the initial proposals and ultimately to becoming part of a larger union, covering workers with many different interests. The article concludes that, irrespective of whether or not amalgamation was inevitable, given the circumstances in Western Australia at the time, its impact upon the rank and file membership was devastating.